Visceral Leishmaniasis with Associated Common, Uncommon, and Atypical Morphological Features on Bone Marrow Aspirate Cytology in Nonendemic Region - Harish Chandra; Smita Chandra; Rajeev Mohan Kaushik (Journal of Tropical Medicine)
Objectives. The present study was conducted to categorise the morphological features on bone marrow aspirate cytology into common, uncommon, and atypical features in a nonendemic region which would be helpful in clinching an early and correct diagnosis especially in clinically unsuspected cases. Methods. The morphological features on bone marrow were categorized into common, uncommon, and atypical in cases of leishmaniasis from non endemic region. Results. Out of total 27 cases, 77.7% were residents of places at the height of 500 m or above and fever was the most common presentation followed by hepatosplenomegaly. Plasmacytosis, hemophagocytosis were the common cytological features while dysmyelopoiesis, presence of leishmania bodies in nonhistiocytic cells, and granuloma with necrosis were uncommon features. Aggregates of LD bodies in form of ring, floret, or strap shapes along with giant cells constitute the atypical morphological features. Conclusion. The knowledge of common, uncommon, and atypical features on bone marrow aspirate cytology is helpful in clinching an early and correct diagnosis of leishmaniasis especially in non endemic areas where clinical suspicion is low. These features will guide the pathologist for vigilant search of LD bodies in the marrow for definite diagnosis and thus will also be helpful in preventing unnecessary workups.